2023
DOI: 10.1101/2023.03.08.531479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term transcutaneous vagus nerve stimulation increases pupil size but does not affect EEG alpha power: a replication

Abstract: Background: Transcutaneous auricular vagus nerve stimulation (taVNS) is a promising brain stimulation method for the treatment of pharmaco-resistant epilepsy and depression. Its clinical efficacy is thought to depend on taVNS-induced activation of the locus coeruleus. However, unlike for invasive VNS, there is little evidence for an effect of taVNS on noradrenergic activity. Objective: We attempted to replicate recently published findings by Sharon et al. (2021), showing that short bursts of taVNS transiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 55 publications
5
9
2
Order By: Relevance
“…Third, in our study, only 8 out of 40 (20%) participants were men, whereas in Neuser et al [1] 34 out of 81 (42%) participants were men. Although this difference could potentially account for the discrepancy between our behavioral results, the limited available evidence suggests that female animals [22] and human participants [35] show larger effects of VNS than males, which is inconsistent with our null finding in a group of mainly female participants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Third, in our study, only 8 out of 40 (20%) participants were men, whereas in Neuser et al [1] 34 out of 81 (42%) participants were men. Although this difference could potentially account for the discrepancy between our behavioral results, the limited available evidence suggests that female animals [22] and human participants [35] show larger effects of VNS than males, which is inconsistent with our null finding in a group of mainly female participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Several recent taVNS studies have not managed to replicate the effects of invasive VNS on psychophysiological measures such as pupil size and P300 amplitude, reporting null effects instead [15][16][17][18]34]. In the present work and another replication attempt [35], we find that even results of high-profile taVNS studies can be difficult to replicate. Parametric exploration of tVNS stimulation parameters [36,37] and demanding authors to report internal replications may help this nascent field of inquiry to overcome these challenges.…”
Section: Discussioncontrasting
confidence: 65%
“…Additionally, there are several differences between the taVNS parameters used in this and in prior studies that may contribute to apparent differences in the relationship between taVNS intensity and pupil dilation. Nine of the prior 16 taVNS studies that examined effects on pupil size reported testing taVNS intensities that overlapped in part or in whole with the taVNS intensity range in the present study (Capone et al, 2021;D'Agostini et al, 2022D'Agostini et al, , 2023Keute et al, 2019;Lloyd et al, 2023;Pandža et al, 2020;Sharon et al, 2021;Skora et al, 2024;Urbin et al, 2021). Another four studies tested taVNS ranges below the minimum intensity in the present study (Burger, Van der Does, et al, 2020;D'Agostini et al, 2021;McHaney et al, 2023;Warren et al, 2019).…”
Section: Variation In Tavns Intensitymentioning
confidence: 71%
“…Location and configuration of the stimulating electrode may also be important. All three experiments in past studies that applied taVNS to the EAM found pupil effects (Capone et al, 2021;Pandža et al, 2020;Urbin et al, 2021), while one of the two experiments that targeted tragus found pupil effects (Villani et al, 2019), and only eight of the 18 experiments in prior studies that targeted the concha found an effect on pupil size (D'Agostini et al, 2023;Lloyd et al, 2023;Sharon et al, 2021;Skora et al, 2024;Urbin et al, 2021;Wienke et al, 2023). This suggests that stimulating the EAM is perhaps more consistently effective in increasing neuromodulatory activity.…”
Section: Variation In Location and Configuration Of The Stimulating E...mentioning
confidence: 97%
See 1 more Smart Citation